2014
DOI: 10.5430/ijdi.v1n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymph node staging by EBUS-TBNA and CT: Characteristics of lymph node enlargement caused by anthracosis and other benign conditions

Abstract: Objectives: Aim of this comparative study was to assess the accuracy of computed tomography (CT) and endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) for mediastinal lymph node staging in cases of lymph node enlargement due to anthracosis and other benign conditions. Methods:In a retrospective analysis we report on the MSCT findings of 39 patients (28 males, 11 females) with EBUS-TBNA confirmed diagnosis of 53 enlarged lymph nodes due to anthracosis. A control group comprised 20 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Endobronchial ultrasound–TBNA is a useful procedure in the identification of anthracotic particles. 6 Kirchner et al 7 examined mediastinal lymph nodes with EBUS–TBNA. Then, the anatomical positions of these lymph nodes were analyzed by multislice computed thorax tomography, and they found that the foremost common location of anthracotic lymph nodes was the subcarinal.…”
Section: Discussionmentioning
confidence: 99%
“…Endobronchial ultrasound–TBNA is a useful procedure in the identification of anthracotic particles. 6 Kirchner et al 7 examined mediastinal lymph nodes with EBUS–TBNA. Then, the anatomical positions of these lymph nodes were analyzed by multislice computed thorax tomography, and they found that the foremost common location of anthracotic lymph nodes was the subcarinal.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, according to the ATS regional lymph node system, the most studied lymph node was subcarinal, with rates of 36%, 39%, and 41.5% in some previous studies [ 14 , 5 , 6 ]. In our study, the most frequently examined lymph node with a rate of 37% was subcarinal and this was consistent with the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kirchner et al, they compared anthracosis and other benign diseases, and they found no difference in size [ 6 ]. In another study by Kirchner et al, they took the malignant patient group and the control group as the anthracosis and found that the lymph nodes of the anthracosis group were smaller [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown hilar or mediastinal lymphadenopathy in 94% of subjects, of which 57% were calcified, pursued by bronchial stenosis and narrowing, with or without atelectasis in 94% of the cases [7]. The enlarged mediastinal lymph nodes recorded by CT are also observed in the majority of patients with this problem; however, this evidence may also appear in those suffering from metastatic lung cancer, sarcoidosis, chronic heart failure, or pneumoconiosis [8,9]. Herein, we evaluate the significance of high attenuated, non-calcified mediastinal and hilar lymph nodes in the diagnosis of anthracosis, and we define the triad of anthracosis with high specificity for diagnosis of anthracosis.…”
Section: Introductionmentioning
confidence: 98%